2007
DOI: 10.1080/13504850600592655
|View full text |Cite
|
Sign up to set email alerts
|

Testing cost vs. profit function

Abstract: The empirical literature on estimation of production technology mostly focuses on estimation of dual cost functions. Estimation of a profit function is not that common. Here, we formally test whether the production technology should be represented by a cost or profit function. We also derive elasticities associated with the long-run profit function from the estimated cost function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Asheim et al (2011) estimated low domestic short-run and long-run price responsiveness of the Norwegian salmon supply (0.091 in the short run and 0.141 in the long-run). In contrast, Steen et al (1997), Asche et al (2007), and Andersen et al (2008) all estimated a long-run domestic salmon supply elasticity of about 1.4 to 1.5. Many of the NSC salmon promotion studies listed in Table 1 adopted some version of the domestic salmon supply elasticity of 1.54 estimated by Steen et al (1997) in their analyses.…”
Section: Norwegian Seafood Export Supply Price Responsementioning
confidence: 94%
“…Asheim et al (2011) estimated low domestic short-run and long-run price responsiveness of the Norwegian salmon supply (0.091 in the short run and 0.141 in the long-run). In contrast, Steen et al (1997), Asche et al (2007), and Andersen et al (2008) all estimated a long-run domestic salmon supply elasticity of about 1.4 to 1.5. Many of the NSC salmon promotion studies listed in Table 1 adopted some version of the domestic salmon supply elasticity of 1.54 estimated by Steen et al (1997) in their analyses.…”
Section: Norwegian Seafood Export Supply Price Responsementioning
confidence: 94%
“…Therefore, we also refer to the PMT, which explains international performance through the successful implementation of strategies (Schmid and Kotulla 2011). This theory postulates that a firm's primary goal is to maximize profits, which can be achieved by maintaining high sales (e.g., through the benefits of market segmentation) and low costs (e.g., through the realization of economies of scale) (Asche, Kumbhakar, and Tveterås 2007; Kumbhakar 2002). For example, firms adapt in foreign countries when the sales-maximizing effect of strategic flexibility and price discrimination is larger than the cost-minimizing effect of economies of scale from international standardization and when the frictions between headquarters and foreign subsidiaries are reduced (Samiee and Roth 1992; Shoham 1996; Shoham and Albaum 1994).…”
Section: Theoretical Foundation and Conceptual Frameworkmentioning
confidence: 99%
“…Asheim et al (2011) reported a low price elasticity of Norwegian salmon supply in both the short run (0.091) and long run (0.141). Steen, Asche, and Salvanes (1997), Asche, Kumbhakar, and Tveterås (2007) and Andersen, Roll, and Tveterås (2008), however, reported higher Norwegian salmon supply elasticities of about 1.4 to 1.5. The export supply elasticities estimated or assumed by studies of the NSC salmon promotion program have ranged from close to zero to 2.0 (Williams and Capps 2017).…”
Section: Methodology and Datamentioning
confidence: 98%